Photosynthesis: energy capture - Blankenship, Robert (Henry Stewart Talks, 2007)
Site of photosynthesis in plants and bacteria, Properties of light and pigments, Phases of energy storage, Photosynthetic antennas and reaction centers, Membrane organization, Energetics and efficiency of photosynthesis
Reviewed at 2022/03/30